2007
DOI: 10.2304/ciec.2007.8.4.301
|View full text |Cite
|
Sign up to set email alerts
|

What Counts in Research? A Survey of Early Years' Mathematical Research, 2000–2005

Abstract: This study reviews 208 articles on early childhood mathematics education sourced from the ERIC database and published between 2000 and 2005 in order to determine the adequacy of the literature. The document analysis identified a heavy emphasis on (1) mathematical concepts and instruction, and (2) articles addressing the school years compared with the prior-to-school years. Overall, this study revealed (1) a lack of peer-reviewed articles that discuss, investigate, examine, or debate early childhood mathematics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 26 publications
0
7
1
2
Order By: Relevance
“…The inclusion of 1141 articles in this review is a significant finding in and of itself. When Fox and Diezmann (2007) published findings from a similar literature review examining early childhood mathematics between 2000 and 2005, only 208 articles met the criteria for inclusion. In just over a decade (between 2005 and 2015), research in early childhood mathematics has grown at a tremendous rate.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The inclusion of 1141 articles in this review is a significant finding in and of itself. When Fox and Diezmann (2007) published findings from a similar literature review examining early childhood mathematics between 2000 and 2005, only 208 articles met the criteria for inclusion. In just over a decade (between 2005 and 2015), research in early childhood mathematics has grown at a tremendous rate.…”
Section: Resultsmentioning
confidence: 99%
“…In a cursory examination of current literature reviews, syntheses, or meta-analyses related to mathematics education, we determined that there were very few articles that presented an overarching view of the literature in early childhood mathematics. In fact, only three literature reviews related specifically to early childhood mathematics were identified (Anthony and Walshaw, 2009; Fox and Diezmann, 2007; Linder et al, 2013). In an effort to move towards a better understanding of this body of work, we also examined alternative reviews of literature related to either the cognitive domain of early childhood education or, specifically, elementary mathematics education, as the parameters for these searches often included kindergarten (age five) through third grade (age eight).…”
Section: Findings From Similar Reviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…Målet for vitenskapelige oversiktsartikler er ofte å samle og analysere kunnskap innenfor et fagområde hvor det er gjort store mengder forskning, men målet kan også vaere å identifisere tematiske områder der lite eller ingen forskning er gjort (Petticrew & Roberts, 2006, s. 2). Siden andre oversiktsartikler har tydet på at det finnes lite forskning på matematikk i barnehageårene (Fox & Diezmann, 2007) var antakelsen som lå til grunn for dette bidraget at kunnskapsstatusen om utvikling av romforståelsen i barnehagen er mangelfull.…”
Section: Formål Med Undersøkelsenunclassified
“…Samlet sett kan screeningprosessen for tidsskrifter, biblioteksdatabaser og forskningskartlegginger visualiseres i denne tabellen: (Fox & Diezmann, 2007). Kvaliteten blir sikret gjennom fagfellevurderingen.…”
Section: Screeningunclassified